2016
DOI: 10.1111/gwat.12457
|View full text |Cite
|
Sign up to set email alerts
|

Application of Large‐Scale Inversion Algorithms to Hydraulic Tomography in an Alluvial Aquifer

Abstract: Large-scale inversion methods have been recently developed and permitted now to considerably reduce the computation time and memory needed for inversions of models with a large amount of parameters and data. In this work, we have applied a deterministic geostatistical inversion algorithm to a hydraulic tomography investigation conducted in an experimental field site situated within an alluvial aquifer in Southern France. This application aims to achieve a 2-D large-scale modeling of the spatial transmissivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…geophysics (Bowling et al 2005;Vogelgesang et al 2020), geological correlation between well stratigraphic logs (Durozoy 1972;Borgomano et al 2008;Jazayeri Noushabadi et al 2011) or geostatistical approaches (Meier et al 1998;de Marsily et al 2005;Mariethoz et al 2010). Other methods based on hydraulic tomography provide promising results to describe the heterogeneity of hydraulic conductivity and storage coefficient in fractured rocks, but also require a largeamount of field data (Illman 2014;Yeh et al 2014;Fischer et al 2017). As already mentioned, the pumping test is one of the main methods used to characterize hydrodynamic properties, but in-depth analysis of the data is required to identify the reservoir structure.…”
Section: Introductionmentioning
confidence: 99%
“…geophysics (Bowling et al 2005;Vogelgesang et al 2020), geological correlation between well stratigraphic logs (Durozoy 1972;Borgomano et al 2008;Jazayeri Noushabadi et al 2011) or geostatistical approaches (Meier et al 1998;de Marsily et al 2005;Mariethoz et al 2010). Other methods based on hydraulic tomography provide promising results to describe the heterogeneity of hydraulic conductivity and storage coefficient in fractured rocks, but also require a largeamount of field data (Illman 2014;Yeh et al 2014;Fischer et al 2017). As already mentioned, the pumping test is one of the main methods used to characterize hydrodynamic properties, but in-depth analysis of the data is required to identify the reservoir structure.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, hydraulic tomography (HT) has shown a great potential for high‐resolution subsurface characterization in numerical studies (Cardiff, Bakhos, et al, 2013; Illman et al, 2008; Illman et al, 2010), laboratory sandboxes (Illman et al, 2007; Liu et al, 2007; Zhao et al, 2016), and field‐scale studies (Berg & Illman, 2011; Cardiff et al, 2012; Fischer et al, 2017; Kuhlman et al, 2008; Liu, Yeh, Wang, Hao, et al, 2020; Zha et al, 2016). Many researchers (such as Cardiff et al, 2009; Cho et al, 2020; Illman et al, 2007; Soueid Ahmed et al, 2015; Yeh & Liu, 2000; Zhao & Illman, 2017) have demonstrated steady‐state HT's ability to estimate hydraulic conductivity or transmissivity heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…For measurements with high correlation and therefore redundancy, the proposed compression approach allows decreasing the computational effort of model inversion. The proposed approach is similar to the method in Fischer et al (2017), but instead of applying PCA to the parameter space and reducing the number of parameters, it is applied to the observation space to express the measurements with a reduced number of fixed measurement component terms, as in Rezaie et al (2012). In meteorological forecasting, PCA has been applied for measurement reduction in data assimilation (Collard et al 2010).…”
Section: Introductionmentioning
confidence: 99%